Influence of electrostatic charge on air-conditioning filters from nanofibrous structures (2019)
The objective of the study is to find out what potential has electrostatic charge on the filtration efficiency of nanofilters. The using of filters with nanofibrous structure (fiber thickness is less than 1 μm) is associated with problems of high-pressure loss, which is caused by high density of the filter layer. The high degree of filtration is achieved, but the costs for ventilators power input is very high. Nanofilters are effective in filtering with problematic lower aerosol fractions which is occurring in a common predominantly urban environment. For this reason, a steel grid was placed in front of the nanofibrous filter layer and a potential difference was created between the grid and the filter element. This treatment causes the capture of coarse particles on the steel grid, and the nanofilter retains mainly particles smaller than 0.5 μm. The main aim of the study is to find out whether it makes sense to supplement the filtration system with the influence of electrostatic charging. The idea is especially about separating larger dust particles on a steel grid and electrostatically charged the nanofilter to increase its efficiency. From the results of the measurements mentioned in the article it is stated that in all fractions of the test sample taken together is achieved an average improvement of 14%.